Prescription psychostimulants for cocaine use disorder: A review from molecular basis to clinical approach. (1st March 2023) - Tardelli, Vitor S.; Berro, Lais F.; Gerra, Gilberto; Tadonio, Leonardo; Bisaga, Adam; Fidalgo, Thiago M.
Abstract: Cocaine use is a public health concern in many countries worldwide, particularly in the Americas and Oceania. Overdose deaths involving stimulants, such as cocaine, have been increasing markedly in North America, especially with concurrent opioid involvement. To date, no pharmacological treatment is available to treat stimulant (including cocaine) use disorders. Prescription psychostimulants (PPs) could be useful to treat cocaine use disorder (CUD) as they share the pharmacological effects with cocaine, as evidenced by a recent meta‐analysis that assessed 38 randomized clinical trials (RCTs). PPs were found to promote sustained abstinence and reduce drug use in patients with CUD. The aim of this paper is to provide a narrative review of the clinical pharmacology of PPs and comment on the current stage of evidence supporting PPs to treat CUD. We also propose a model of care that integrates PPs with evidence‐based psychosocial interventions (such as cognitive‐behavioural therapy [CBT] and contingency management [CM]), a harm reduction approach and case management with social support. Abstract : Prescription psychostimulants (PPs) have been proposed as pharmacotherapies for cocaine use disorder (CUD). Preclinical evidence suggests that PPs attenuate the abuse‐related effects of cocaine by reducing its effects on brain dopamine, but not serotonin, levels. In clinical studies, PPs have been shown to promote sustained abstinence and reduce drug use in patients with CUD. A model of care that integrates PPs with evidence‐based psychosocial interventions, harm reduction approaches and social support, may be an effective treatment approach for CUD.